Polyurethane-based solid electrolyte as well as preparation method and application thereof
By combining the three-dimensional skeleton film of metal organic frame with the composite polyurethane layer, the ion transport performance and mechanical properties are synergistically improved by hydrogen bonding, the problem of insufficient ion conductivity and lithium ion migration of existing solid electrolytes is solved, and the lithium battery is significantly improved performance and security.
Patent Information
- Application Number
- CN202411434191.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polymer-based composite solid electrolytes have insufficient ion conductivity and lithium ion migration at room temperature, and have low mechanical properties, making it difficult to effectively inhibit the growth of lithium dendrites, affecting the safety of lithium batteries.
The three-dimensional frame film of metal organic frame is combined with the composite polyurethane layer to jointly improve ion transport performance and mechanical properties through hydrogen bonding. The electrolyte includes a three-dimensional frame film of metal organic frames on a modified glass fiber cloth, and metal organic frame particles embedded in a polymer network of polyurethane in situ.
It significantly improves the room temperature ion conductivity and lithium ion migration number of solid-state batteries, improves the charge and discharge stability, and improves the rate performance and long-term cycle stability of the battery, while enhancing the mechanical properties of the electrolyte.
Smart Images

Figure CN119481256A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid electrolytes, and in particular to a polyurethane-based solid electrolyte and a preparation method and application thereof. Background Art
[0002] Compared with traditional lithium-ion batteries, solid-state batteries have the advantages of high safety and high energy density, in which solid electrolytes play a key role, and therefore have received widespread attention from industry and academia. Polymer-based composite solid electrolytes have the advantages of high flexibility, light weight, easy film formation and low cost, and have great development potential. However, as the main component of high-performance batteries, the current polymer-based composite solid electrolytes still need to significantly improve their ionic conductivity and lithium ion migration number at room temperature. In addition, the strength and modulus of polymer materials are low, and need to be significantly improved to effectively inhibit the growth of lithium dendrites, thereby improving the safety of lithium batteries.
[0003] Polyurethane is a block copolymer that can be synthesized by addition reaction of polyols and diisocyanates. It has an incompatible "soft segment-hard segment" two-phase structure. It is attracting attention due to its strong structural designability, good bulk mechanical properties, and ability to be cured in situ to solve electrolyte and interface problems. At present, the conduction mechanism of lithium ions in polyurethane-based polyethylene is roughly the same as that of block copolymer electrolytes. The soft segment provides Li + The hard segment provides structural rigidity and is the main repeating unit in polyurethane. The carbamate group is able to form hydrogen bonds in the polymer network, which can enhance the strength of the polymer on the one hand and provide sites for interaction with lithium salts on the other hand, promote the dissociation of lithium salts and enhance ion conduction. However, the glass transition temperature of common polyurethanes is relatively high, and there is also partial crystallization behavior, which leads to the generally low ion conductivity of polyurethane electrolytes. Therefore, a linear polyurethane solid electrolyte containing a comb or star shape is prepared in patent application CN114300740A, and the ion transport capacity of polyurethane is improved by adding side chains. In order to further improve the ionic conductivity and mechanical properties of polyurethane-based electrolytes, attempts have been made to add inorganic fillers. As mentioned in patent application CN112117488A, the ion transport performance of polyurethane-based electrolytes can be improved by blending lithium lanthanum titanium oxide particles with linear polyurethane. However, although the patent application CN114195978A discloses a method for preparing a solid electrolyte by compounding MIL-101(Cr) and polyurethane, and claims that its conductivity has been significantly improved; in practice, its conductivity still cannot exceed 10 -4S / cm; because this simple inorganic / organic blend cannot significantly improve the ionic conductivity of the electrolyte. Patent application CN117691199A introduces a method for preparing a glass fiber-based composite material, which pre-treats the glass fiber base with oxides and epoxy resins, and then coats the polymer matrix layer to improve the mechanical strength and ionic conductivity of the material, and reduce the crystallinity of the polymer matrix layer to inhibit the growth of lithium dendrites. However, the room temperature ionic conductivity of its solid electrolyte is only 10 -5 S / cm level, and the tensile strength is about 33MPa.
[0004] In summary, existing polymer-based composite solid electrolytes have shown significant advantages in ionic conductivity, ion migration number, fracture toughness, and improving the interface between electrolyte and electrode; however, as electrolytes for high-performance lithium batteries, their ionic conductivity is still insufficient. How to further improve ionic conductivity and lithium ion migration number at room temperature remains a research focus and difficulty in the field of solid electrolyte technology. Summary of the invention
[0005] The purpose of the present application is to provide an improved polyurethane-based solid electrolyte and a preparation method and application thereof.
[0006] In order to achieve the above objectives, this application adopts the following technical solutions:
[0007] On one hand, the present application discloses a polyurethane-based solid electrolyte, comprising a metal organic framework three-dimensional skeleton film and a composite polyurethane layer attached to its surface; the metal organic framework three-dimensional skeleton film is a glass fiber cloth modified by a metal organic framework; the composite polyurethane layer comprises polyurethane and metal organic framework particles of a polymer network in situ embedded in the polyurethane; the repeating unit carbamate group in the polyurethane forms a hydrogen bond with the metal organic framework three-dimensional skeleton, synergistically improving the ion transport performance and mechanical properties.
[0008] It should be noted that the polyurethane-based solid electrolyte of the present application effectively solves the problem of poor ion conductivity and lithium ion migration number of solid-state batteries, and also solves the interface problem between the positive electrode and the electrolyte, thereby improving the rate performance and long-term cycle stability of lithium-ion solid-state batteries. The present application uses a metal organic framework with a high specific surface area to modify the surface of the glass fiber cloth, which can promote the dissociation of lithium salts and inhibit the migration of anions, thereby improving ionic conductivity and ion migration number, and improving charge and discharge stability. In addition, a large number of repeating unit carbamate groups in polyurethane form hydrogen bonds with the three-dimensional skeleton of the metal organic framework, and the two form a synergistic effect, further promoting the rapid transmission of lithium ions, and increasing the migration number of the polymer electrolyte, improving the ion transmission performance and mechanical properties.
[0009] In one implementation of the present application, polyurethane is synthesized by reacting isocyanate and diol.
[0010] In one implementation of the present application, the isocyanate is at least one of isocyanate (IPDI), hexamethylene diisocyanate (HDI), diphenylmethane-4,4'-diisocyanate (MDI), toluene diisocyanate (TDI) and isophorone diisocyanate (IPDI).
[0011] In one implementation of the present application, the diol is at least one of polytetramethylene glycol (PTMG), polycarbonate diol (PCDL), polypropylene glycol (PPG) and polyethylene glycol (PEG).
[0012] In one implementation of the present application, the molecular weight of the diol is at least one of 800, 1000, 1200, 1500, 2000, 4000, 5000, 6000 and 8000.
[0013] In one implementation of the present application, the metal organic framework is MOF-5 (Zn4O(BDC)3), MIL-53 (Al) (AlO4(OH) (BDC)), HKUST-1 (Cu3(BTC)2), MIL-101 (M3O(BTC)2OH(H2O)2), ZIF-1, ZIF-2, ZIF-3, ZIF-4, ZIF-5, ZIF-6, ZIF-7, ZIF-8, ZIF-9, Z At least one of IF-10, ZIF-22, ZIF-69, ZIF-90, NAFS-1, MIL-47, CAU-1, MIL-101(Cr), CPO-27-Mg, CPO-27-Mn, CPO-27-Co, CPO-27-Ni, CPO-27-Zn, Mn(HCOO)2, Co(HCOO)2, Ni(HCOO)2, MOF-74, zirconium-based MOF, and hafnium-based MOF.
[0014] In the present application, BDC is 1,4-benzenedicarboxylate, BTC is 1,3,5-benzenetricarboxylate, and M in M3O(BTC)2OH(H2O)2 is Al, Cr or Fe.
[0015] In one implementation of the present application, the zirconium-based MOF is at least one of UiO-66(Zr)(Zr6O4(OH)4(BDC)6), UiO-67(Zr)(Zr6O4(OH)4(BPDC)6), UiO-68(Zr)(Zr6O4(OH)4(TPDC)6), UiO-66-OH(Zr), UiO-67-OH(Zr), UiO-68-OH(Zr), UiO-66-NH2(Zr), UiO-67-NH2(Zr), UiO-68-NH2(Zr), UiO-66-4F(Zr), UiO-66-2F(Zr), UiO-66-CF3(Zr), UiO-66-SO3(Zr), UiO-67-SO3(Zr), and UiO-68-SO3(Zr).
[0016] In one implementation of the present application, the hafnium-based MOF is at least one of UiO-66(Hf)(Hf6O4(OH)4(BDC)6), UiO-67(Hf)(Hf6O4(OH)4(BPDC)6), UiO-68(Hf)(Hf6O4(OH)4(TPDC)6), UiO-66-OH(Hf), UiO-67-OH(Hf), UiO-68-OH(Hf), UiO-66-NH2(Hf), UiO-67-NH2(Hf), UiO-68-NH2(Hf), UiO-66-4F(Hf), UiO-66-2F(Hf), UiO-66-CF3(Hf), UiO-66-SO3(Hf), UiO-67-SO3(Hf), and UiO-68-SO3(Hf).
[0017] In the present application, BPDC is dimethyl biphenyl dicarboxylate, TPDC is terphenyl-4,4'-dicarboxylate,
[0018] In one implementation of the present application, the glass fiber cloth is at least one of glass fiber woven cloth, glass fiber non-woven cloth, and glass fiber filter membrane.
[0019] In one implementation of the present application, the unit weight of the glass fiber cloth is 10 to 200 g / m 2 , the thickness of the glass fiber cloth is 10 to 100 μm.
[0020] In one implementation of the present application, the metal organic framework three-dimensional skeleton film is a three-dimensional porous skeleton formed by in-situ growth of the metal organic framework on the glass fiber cloth.
[0021] In one implementation of the present application, the loading rate of the metal organic framework on the metal organic framework three-dimensional skeleton film is 5 to 30%.
[0022] In one implementation of the present application, the thickness of the polyurethane-based solid electrolyte is 30 to 250 μm.
[0023] Another aspect of the present application discloses a method for preparing the polyurethane-based solid electrolyte of the present application, comprising the following steps:
[0024] a) mixing diisocyanate, diol, lithium salt, organic solvent and catalyst under inert atmosphere, heating and stirring to obtain a prepolymer;
[0025] b) adding a chain extender, a plasticizer and metal organic framework particles to the prepolymer, and continuing heating and stirring to obtain a polyurethane solution;
[0026] c) coating the polyurethane solution on the metal organic framework three-dimensional skeleton film and drying it to obtain the polyurethane-based solid electrolyte of the present application.
[0027] In one implementation of the present application, in step a) and step b), the amount of isocyanate is 10 to 100 parts by weight, the amount of diol is 100 to 500 parts by weight, the amount of chain extender is 1 to 5 parts by weight, the amount of catalyst is 0.5 to 1 part by weight, the amount of lithium salt is 30 to 150 parts by weight, the amount of organic solvent is 500 to 1000 parts by weight, the amount of plasticizer is 5 to 50 parts by weight, and the amount of metal organic framework particles is 1 to 25 parts by weight.
[0028] In one implementation of the present application, the chain extender is at least one of 2,2-dihydroxymethylbutyric acid, bis(2-hydroxyethyl) disulfide, 1,4-butanediol (BDO), 2-hydroxyethyl acrylate, N-methyldiethanolamine, methylpropylene glycol, diethylene glycol and polycaprolactone triol (PCL).
[0029] In one implementation of the present application, the catalyst is dibutyltin dilaurate (DBTDL).
[0030] In one implementation of the present application, the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate (LiCF3SO3).
[0031] In one implementation of the present application, the organic solvent is at least one of tetrahydrofuran (THF), chloroform, N,N-dimethylformamide (DMF), butanone (MEK), dichloromethane (DCM) and dimethyl sulfoxide (DMSO).
[0032] In one implementation of the present application, the plasticizer is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, succinonitrile and 3-methyl-2-oxazolidinone.
[0033] In one implementation of the present application, the temperature of heating and stirring in step a) is 50-80° C., the stirring speed is 600-1200 rpm, and the heating and stirring time is 8-15 hours.
[0034] In one implementation of the present application, the inert atmosphere in step a) is a nitrogen atmosphere or an argon atmosphere.
[0035] In one implementation of the present application, the temperature of heating and stirring in step b) is 50-80° C., the stirring speed is 600-1200 rpm, and the heating and stirring time is 2-5 hours.
[0036] In one implementation of the present application, the drying method in step c) is vacuum drying.
[0037] In one implementation of the present application, the vacuum drying condition in step c) is drying at 60-100° C. for 12-24 hours.
[0038] In one implementation of the present application, a method for preparing a metal-organic framework three-dimensional skeleton film includes immersing a surface-treated glass fiber cloth in a precursor solution of the metal-organic framework, heating, in-situ synthesizing the metal-organic framework on the surface of the glass fiber cloth, and then washing and drying to obtain the metal-organic framework three-dimensional skeleton film.
[0039] In one implementation of the present application, the surface treatment of the glass fiber cloth includes soaking the glass fiber cloth in a solution of a surface treatment agent, and then taking it out and drying it to obtain the surface-treated glass fiber cloth.
[0040] In one implementation of the present application, the surface treatment agent includes a silane coupling agent and / or dopamine.
[0041] In one implementation of the present application, the silane coupling agent is at least one of isobutyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane and vinyltriethoxysilane.
[0042] In one implementation of the present application, the solution of the surface treatment agent is an aqueous solution of the surface treatment agent.
[0043] In one implementation of the present application, the solution of the surface treatment agent is obtained by dissolving the surface treatment agent in deionized water at a volume ratio or weight ratio of 1:200 to 1:5.
[0044] In one implementation of the present application, the glass fiber cloth is immersed in a solution of the surface treatment agent, specifically comprising immersing the glass fiber cloth in the solution of the surface treatment agent for 0.01 to 24 hours; then, taking out the glass fiber cloth, rinsing it with deionized water and / or ethanol, and then drying it at 80 to 120°C.
[0045] In one implementation of the present application, the preparation method of the present application further comprises pre-activating the prepared metal organic framework three-dimensional skeleton film, and then coating the urethane solution on the activated metal organic framework three-dimensional skeleton film.
[0046] In one implementation of the present application, the activation treatment method is to heat the prepared metal organic framework three-dimensional skeleton film at 120 to 150° C. for 24 to 48 hours.
[0047] Another aspect of the present application discloses the application of the polyurethane-based solid electrolyte of the present application in a lithium metal battery or a lithium ion battery.
[0048] Another aspect of the present application discloses a lithium metal battery or a lithium ion battery, which adopts the polyurethane-based solid electrolyte of the present application.
[0049] It should be noted that the lithium metal battery or lithium ion battery of the present application has high ionic conductivity and ion migration number due to the use of the polyurethane-based solid electrolyte of the present application, which effectively solves the problem of poor ionic conductivity and lithium ion migration number of lithium metal solid-state batteries or lithium ion solid-state batteries, and also solves the interface problem between the positive electrode and the electrolyte, thereby improving the rate performance and long-term cycle stability of lithium metal solid-state batteries or lithium ion solid-state batteries.
[0050] Due to the adoption of the above technical solution, the beneficial effects of this application are:
[0051] The polyurethane-based solid electrolyte of the present application can promote the dissociation of lithium salts and inhibit the migration of anions, thereby improving the ionic conductivity and the ion migration number and improving the charge and discharge stability; a large number of repeating unit carbamate groups in the polyurethane form hydrogen bonds with the three-dimensional skeleton of the metal organic framework, and the two form a synergistic effect, further promoting the rapid transmission of lithium ions, and increasing the migration number of the polymer electrolyte, thereby improving the ion transmission performance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a schematic diagram of the polyurethane structure in the embodiment of the present application;
[0053] Figure 2 This is a schematic diagram of polyurethane synthesis in the embodiment of the present application;
[0054] Figure 3 is a scanning electron microscope image of a cross section of a polyurethane electrolyte in an embodiment of the present application;
[0055] Figure 4 is the charge and discharge curve of lithium iron phosphate to lithium in the embodiment of the present application;
[0056] Figure 5 It is the tensile curve of the polyurethane-based solid electrolyte in the embodiment of the present application. DETAILED DESCRIPTION
[0057] The present application has developed a new composite polyurethane solid electrolyte based on MOF three-dimensional skeleton support, namely the polyurethane-based solid electrolyte of the present application: comprising a metal organic framework three-dimensional skeleton film and a composite polyurethane layer attached to its surface; the metal organic framework three-dimensional skeleton film is a glass fiber cloth modified by a metal organic framework; the composite polyurethane layer comprises polyurethane and metal organic framework particles of a polymer network in situ embedded in polyurethane; the repeating unit carbamate group in the polyurethane forms a hydrogen bond with the metal organic framework three-dimensional skeleton, synergistically improving the ion transport performance and mechanical properties. The polyurethane-based solid electrolyte of the present application can be used as a component of a high-performance lithium battery or structural battery.
[0058] Compared with the existing polyurethane solid electrolyte, the polyurethane-based solid electrolyte of the present application has the following advantages:
[0059] (1) In-situ synthesis of polyurethane to solve the interface problem between electrolyte and electrode.
[0060] (2) MOF particles are in situ embedded in the polymer network of polyurethane, providing more sites for lithium ion transmission.
[0061] (3) The repeating unit carbamate group in polyurethane forms hydrogen bonds with the three-dimensional skeleton of MOF, synergistically improving the ion transport performance and mechanical properties.
[0062] (4) The MOF three-dimensional skeleton provides a continuous lithium ion transmission path, improving ionic conductivity.
[0063] (5) The microporous structure of MOF can selectively confine larger anions and achieve high ion transmission numbers.
[0064] (6) MOFs have high surface energy and strong adsorption capacity, which can capture undesirable impurities and by-products in the system, inhibit side reactions, and have high chemical stability.
[0065] (7) The structure of MOF is highly designable, controllable, and modifiable, providing broad space for the optimization of its function.
[0066] (8) The combination of MOF and glass fiber is close to the mechanical properties of fiber-reinforced composites and meets the requirements of structural batteries.
[0067] (9) It can realize the large-scale preparation of ultra-thin composite solid electrolytes.
[0068] These advantages make the MOF-modified glass fiber composite polyurethane solid electrolyte of the present application have broad application prospects and provide a new solution for the development of solid-state batteries.
[0069] The polymer composite solid electrolyte disclosed in the present invention effectively solves the problems of ion conductivity and poor lithium ion migration number of solid-state batteries, while also solving the interface problem between the positive electrode and the electrolyte, thereby improving the rate performance and long-term cycle stability of lithium-ion solid-state batteries.
[0070] The present application is further described in detail below through specific examples and drawings. The following examples are only used to further illustrate the present application and should not be construed as limiting the present application.
[0071] The terms used in this application, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The methods used in the following examples are conventional methods unless otherwise specified, and the raw materials used can be obtained from public commercial channels unless otherwise specified. Unless otherwise specified, all operations are carried out at normal temperature and pressure.
[0072] Embodiment 1
[0073] In this example, diisocyanate (IPDI), diol PTMG1000, lithium salt LiTFSI, organic solvent tetrahydrofuran (THF), catalyst DBTDL, plasticizer succinonitrile (SN), chain extender BDO and metal organic framework particles UiO-66 are used to prepare a polyurethane solution, and UiO-66-NH2-modified glass fiber cloth is used as the metal organic framework three-dimensional skeleton film. The polyurethane solution is coated on the UiO-66-NH2-modified glass fiber cloth to form the polyurethane-based solid electrolyte of this example.
[0074] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0075] a) In a glove box filled with inert gas, 0.60 g of diisocyanate (IPDI), 2.00 g of diol PTMG1000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 ml of tetrahydrofuran THF, 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C. and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0076] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 5 wt%, a chain extender BDO (0.06 g), and a MOFs filler UiO-66 with a final concentration of 10 wt% to the prepolymer, and then stirring and reacting at 50° C. and 900 rpm for 3 hours to obtain a uniform polyurethane MOF solution.
[0077] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0078] d) The surface treated glass fiber cloth (commercial electronic grade glass cloth 106) was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0079] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0080] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0081] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example, which is marked as PUM1.
[0082] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0083] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0084] Embodiment 2
[0085] This example adopts the same method and materials as in Example 1 to prepare a polyurethane-based solid electrolyte, the only difference being that an equal amount of diol PTMG2000 is used to replace the diol PTMG1000 in Example 1, and the rest is the same as in Example 1.
[0086] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0087] a) In a glove box filled with inert gas, 0.3 g of diisocyanate (IPDI), 2.00 g of diol PTMG2000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran THF, 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C. and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0088] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 5 wt%, a chain extender BDO of 0.03 g, and a MOFs filler UiO-66 with a final concentration of 10 wt% to the prepolymer, and then stirring and reacting at 50° C. and 900 rpm for 3 hours to obtain a uniform polyurethane MOF solution.
[0089] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0090] d) The surface treated glass fiber cloth was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0091] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0092] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0093] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example, which is labeled as PUM2.
[0094] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0095] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0096] Embodiment 3
[0097] In this example, the polyurethane-based solid electrolyte is prepared by the same method and materials as in Example 2, with the only difference being that an equal amount of diphenylmethane-4,4'-diisocyanate (MDI) is used to replace the diisocyanate (IPDI) in Example 2, and an equal amount of chain extender PCL is used to replace the chain extender BDO in Example 2, and the rest is the same as in Example 2.
[0098] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0099] a) In a glove box filled with inert gas, 0.34 g of diphenylmethane-4,4'-diisocyanate (MDI), 2 g of diol PTMG2000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran THF, 0.5 wt% of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C., and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:MDI was 1:2.
[0100] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 5 wt%, 2.37 g of a chain extender PCL and a MOFs filler UiO-66 with a final concentration of 10 wt% to the prepolymer, and then stirring and reacting at 50° C. and 900 rpm for 3 hours to obtain a uniform polyurethane MOF solution.
[0101] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0102] d) The surface treated glass fiber cloth was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0103] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0104] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0105] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example, which is labeled as PUM3.
[0106] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0107] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0108] Embodiment 4
[0109] In this example, the polyurethane-based solid electrolyte is prepared by the same method and materials as in Example 2. The only difference is that the chain extender PCL is used to replace the chain extender BDO in Example 2 in an equal amount, and the amount of plasticizer succinonitrile (SN) is increased. The rest is the same as in Example 2.
[0110] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0111] a) In a glove box filled with inert gas, 0.30 g of diisocyanate IPDI, 2.00 g of diol PTMG2000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran THF, 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C., and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0112] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 10 wt%, 0.11 g of a chain extender PCL and a MOFs filler UiO-66 with a final concentration of 10 wt% to the prepolymer, and then stirring and reacting at 50° C. and 900 rpm for 3 hours to obtain a uniform polyurethane MOF solution.
[0113] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0114] d) The surface treated glass fiber cloth was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0115] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0116] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0117] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example, which is labeled as PUM4.
[0118] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0119] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0120] Embodiment 5
[0121] In this example, the same method and materials as in Example 4 were used to prepare a polyurethane-based solid electrolyte, with the only difference being that an equal amount of MIL-101 was used to replace UiO-66 in Example 4 to prepare a polyurethane MOF solution, and the rest was the same as in Example 4.
[0122] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0123] a) In a glove box filled with inert gas, 0.30 g of diisocyanate IPDI, 2.00 g of diol PTMG2000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran THF, 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C., and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0124] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 10 wt%, 0.11 g of a chain extender PCL and a MOFs filler MIL-101 with a final concentration of 10 wt% to the prepolymer, and then stirring and reacting at 50° C. and 900 rpm for 3 hours to obtain a uniform polyurethane MOF solution.
[0125] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0126] d) The surface treated glass fiber cloth was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0127] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0128] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0129] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example, which was labeled as PUM5.
[0130] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0131] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0132] Embodiment 6
[0133] In this example, based on Example 1, different MOFs fillers were used to prepare the polyurethane MOF solution, and the remaining steps and parameters were the same as those in Example 1.
[0134] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0135] a) In a glove box filled with inert gas, 0.60 g of diisocyanate (IPDI), 2.00 g of diol PTMG1000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran (THF), 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C., and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0136] b) Adding a plasticizer succinonitrile (SN) with a final concentration of 5 wt%, a chain extender BDO of 0.06 g, and a MOFs filler with a final concentration of 10 wt% to the prepolymer, and then stirring at 900 rpm at 50° C. for 3 hours to obtain a uniform polyurethane MOF solution. The specific MOFs fillers added in this example are shown in Table 1.
[0137] c) The MOF precursor solution was prepared by solvent thermal synthesis method. The preparation of the MOF precursor solution is shown in Table 1.
[0138] d) The surface treated glass fiber cloth was immersed in the MOF precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0139] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0140] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0141] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example.
[0142] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0143] Table 1 MOFs filler and MOF precursor solution of MOF three-dimensional skeleton used in this example
[0144]
[0145] Different polyurethane-based solid electrolytes were prepared according to Table 1. The polyurethane-based solid electrolytes of Experiments 1 to 5 were marked as PUM6-1, PUM6-2, PUM6-3, PUM6-4, and PUM6-5, respectively.
[0146] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0147] Embodiment 7
[0148] Based on Example 1, this example tests the effects of different MOFs filler addition amounts in the polyurethane MOF solution on the solid electrolyte, and the remaining steps and parameters are the same as those in Example 1.
[0149] The preparation method of the polyurethane-based solid electrolyte in this example comprises the following steps:
[0150] a) In a glove box filled with inert gas, 0.60 g of diisocyanate (IPDI), 2.00 g of diol PTMG1000 and 1.00 g of lithium salt LiTFSI were dissolved in 10 mL of tetrahydrofuran (THF), 0.5 wt % of DBTDL was added to the solution as a reaction catalyst, the mixed solution was heated at 50° C., and stirred at 1200 rpm for 12 hours in a glove box filled with inert gas to obtain a prepolymer. The final molar ratio of monomer PTMG:IPDI was 1:2.
[0151] b) Add 5 wt% plasticizer succinonitrile (SN), 0.06 g chain extender BDO and MOFs filler UiO-66 to the prepolymer, and then react at 50°C for 3 hours to obtain a uniform polyurethane MOF solution. In this example, polyurethane MOF solutions with MOFs filler concentrations of 1%, 5%, 10%, 15%, 20%, and 30% were prepared.
[0152] c) Using a solvothermal synthesis method, 0.70 g of zirconium tetrachloride and 0.54 g of 2-aminoterephthalic acid were added to 45 ml of acetone and 45 ml of DMF, and ultrasonically dissolved for 10 minutes to obtain a UiO-66-NH2 precursor solution.
[0153] d) The surface treated glass fiber cloth was immersed in the UiO-66-NH2 precursor solution, placed in a polytetrafluoroethylene reactor, and heated at 120° C. for 24 hours.
[0154] e) washing the product of step d) with DMF and methanol three times respectively, drying at 120° C. in vacuum for 24 hours, and activating at 150° C. for 24 hours to obtain a MOF three-dimensional framework with a loading rate of 25%.
[0155] f) After degassing the polyurethane MOF solution obtained in step b) under vacuum, coating it on the MOF three-dimensional skeleton using a coating machine with a 100 μm coater.
[0156] g) Then, the mixture was dried in a vacuum oven at 60° C. for 12 hours to obtain an electrolyte membrane, namely the polyurethane-based solid electrolyte of this example.
[0157] The polyurethane-based solid electrolytes prepared from polyurethane MOF solutions with MOFs filler concentrations of 1%, 5%, 10%, 15%, 20%, and 30% are labeled PUM7-1, PUM7-2, PUM7-3, PUM7-4, PUM7-5, and PUM7-6, respectively.
[0158] After complete drying, the membrane was immediately transferred to a glove box with water and oxygen contents less than 0.1 ppm and stored in an argon environment until use.
[0159] The polyurethane-based solid electrolyte membrane prepared in this example was cut into discs with a diameter of 16 mm, and assembled into 2032 button cells with lithium iron phosphate positive electrode plates (commercial positive lithium iron phosphate, D-3, Kelude) and lithium metal negative electrodes (commercial lithium plates, 14 mm, Ganfeng Lithium). At the same time, lithium-to-lithium symmetric batteries (2032 button cells) were assembled. The battery assembly was carried out in a glove box, and the button cells (CR2032 type) were assembled in a glove box filled with argon (H2O and O2 content <0.01ppm). The assembly process is stacked in the order of negative electrode shell, spring sheet, stainless steel gasket, lithium sheet, solid electrolyte membrane, positive electrode sheet, and positive electrode shell.
[0160] Comparative Example 1
[0161] The preparation method of the polyurethane-based solid electrolyte comprises the following steps:
[0162] (1) 0.60 g of IPDI diisocyanate, 2.00 g of PTMG1000 diol and 1.00 g of LiTFSI lithium salt were dissolved in 10 mL of tetrahydrofuran (THF). 0.5 wt% of DBTDL was added to the solution as a reaction catalyst. The final molar ratio of monomers (PTMG:IPDI) was 1:2.
[0163] (2) The mixed solution was heated at 50° C. and stirred in a glove box filled with inert gas for 12 hours to fully react.
[0164] (3) 5 wt% of plasticizer succinonitrile SN, 0.60 g of chain extender BDO and 10 wt% of MOFs filler UiO-66 were dissolved in the mixed solution obtained in the first step, and then reacted at 50° C. for 3 hours to obtain a uniform polyurethane MOF solution.
[0165] (4) The solution obtained in (3) is degassed under vacuum and then coated on a glass fiber cloth.
[0166] (5) Then, the electrolyte membrane was dried in a vacuum oven at 60°C for 12 hours. After complete drying, the membrane was immediately transferred to a glove box (water and oxygen content less than 0.1 ppm, argon atmosphere).
[0167] (6) The solid electrolyte membrane is cut into discs with a diameter of 16 mm, and assembled into a battery with a lithium iron phosphate positive electrode and a lithium metal negative electrode. At the same time, a lithium-to-lithium symmetrical battery is assembled. The battery assembly is the same as in Example 1.
[0168] Comparative Example 2
[0169] The preparation method of the polyurethane-based solid electrolyte comprises the following steps:
[0170] (1) 0.03 g of IPDI diisocyanate, 2.00 g of PTMG2000 diol and 1.00 g of LiTFSI lithium salt were dissolved in 10 mL of tetrahydrofuran (THF). 0.5 wt% of DBTDL was added to the solution as a reaction catalyst. The final molar ratio of monomers (PTMG:IPDI) was 1:2.
[0171] (2) The mixed solution was heated at 50° C. and stirred in a glove box filled with inert gas for 12 hours to fully react.
[0172] (3) 5 wt% of plasticizer succinonitrile SN, 0.03 g of chain extender BDO and 10 wt% of MOFs filler UiO-66 were dissolved in the mixed solution obtained in the first step, and then reacted at 50° C. for 3 hours to obtain a uniform polyurethane MOF solution.
[0173] (4) The solution obtained in (3) is degassed under vacuum and then coated on a glass fiber cloth.
[0174] (5) Then, the electrolyte membrane was dried in a vacuum oven at 60°C for 12 hours. After complete drying, the membrane was immediately transferred to a glove box (water and oxygen content less than 0.1 ppm, argon atmosphere).
[0175] (6) The solid electrolyte membrane is cut into discs with a diameter of 16 mm, and assembled into a battery with a lithium iron phosphate positive electrode and a lithium metal negative electrode. At the same time, a lithium-to-lithium symmetrical battery is assembled. The battery assembly is the same as in Example 1.
[0176] The cross section of the polyurethane-based solid electrolyte prepared in the above embodiment was observed by scanning electron microscopy. The results showed that the thickness of the polyurethane-based solid electrolyte membrane prepared in the embodiment was about 60 μm. Figure 3 shown. Figure 3 This is a cross-sectional scanning electron microscope image of the polyurethane-based solid electrolyte membrane prepared in Example 4. It is analyzed that the thickness of the polyurethane-based solid electrolyte membrane is about 60 μm, which is moderate and can effectively improve the overall performance of the battery. An overly thick electrolyte layer will increase the internal resistance of the battery, hinder the conduction efficiency of ions in the electrolyte, and cause the power density and energy density of the battery to decrease. This is because the longer ion transmission path increases the electrochemical resistance, resulting in an increase in the internal voltage drop of the battery, thereby affecting the charge and discharge efficiency and cycle life. If the thickness of the solid electrolyte is too thin, although it can reduce the distance of ion transmission and improve conductivity, it will also bring many challenges. If the electrolyte layer is too thin, it may not be able to fully cover the supporting material, such as a glass fiber substrate, resulting in uneven coverage on the electrolyte membrane and the formation of microscopic defects. These defects increase the risk of short circuits in the battery, especially when using a lithium metal negative electrode, which can easily cause dendrite growth. These dendrites can pierce the thin film electrolyte, further causing the battery to short circuit and reduce safety.
[0177] The ionic conductivity and lithium ion migration number of Examples 1 to 7, and Comparative Examples 1 and 2 were tested, and the test results are shown in Table 2.
[0178] The test of ionic conductivity generally adopts AC impedance spectroscopy technology. The prepared polymer electrolyte is cut into small discs (diameter 16mm), and then sandwiched between two stainless steel electrodes (SS) to assemble into SS / electrolyte / SS blocking electrode. The AC impedance spectrum of the blocking electrode is tested by an electrochemical workstation to indirectly obtain the bulk resistance Rb. The AC impedance spectrum test frequency range is 5×10 5 Hz to 0.1Hz, and the test temperature range is 25℃ to 60℃.
[0179] The conductivity of the electrolyte (σ, S / cm) can be calculated by the following formula:
[0180] σ=L÷(R b ×S)
[0181] Where, σ is the ionic conductivity (S / cm), L is the thickness of the electrolyte membrane (cm), and S is the electrode area (cm 2 ), Rb is the body resistance (Ω). In the AC impedance spectrum, Rb is the resistance corresponding to the intersection of the incomplete semicircle in the high-frequency part and the real axis.
[0182] The lithium transfer number (tLi+) was tested in a symmetrical lithium battery at room temperature using an IVIUMnSTAT by combining DC polarization and AC impedance measurement. A DC potential (ΔV = 10mV) was applied for 7200 seconds to obtain the initial current and the steady-state current. At the same time, the AC impedance spectrum of the same battery was measured before and after polarization. The tLi+ value was calculated using the following formula:
[0183]
[0184] Where ΔV represents the potential difference applied to the battery; R 0 el and R ss el They are the resistance of the electrode under initial and steady-state conditions respectively. The electrode resistance is the sum of the charge transfer resistance and the resistance of the electrode passivation layer.
[0185] The electrochemical stability window is an important indicator for evaluating the performance of electrolytes. The assembled lithium metal electrode / / stainless steel electrode asymmetric battery has a stable electrochemical performance at 0.5 mV s at room temperature. -1 The electrochemical stability of the polyurethane-based electrolyte was evaluated by linear sweep voltammetry (LSV) at a scan rate of 2 to 7 V.
[0186] The cycling performance of polyurethane-based electrolyte batteries was measured by lithium metal batteries (LFP / / Li) using a new battery test system (BTS-5V 10mA). The all-solid-state lithium battery test was carried out by placing the battery in a constant temperature drying oven at 30°C, with a charge and discharge current of 1C = 170mA / g (calculated based on the theoretical capacity of lithium iron phosphate 170mAh / g), and a charge and discharge voltage range of 2.8-3.9V. The test results are shown in Table 2, and some of the results are shown in Table 2. Figure 4 shown. Figure 4 This is the test result of the battery of Example 4 at 5C.
[0187] The tensile strength of the polyurethane-based solid electrolyte was tested using a universal testing machine (500N zwickiLine, ZwickRoell). The tensile test sample preparation was as follows: 2cm*8cm specimens were cut in the glove box, wrapped with plastic wrap, and taken out of the glove box for testing. The test results are shown in Table 2. Some of the results are shown in Figure 5 As shown, Figure 5 It is the stretching curve diagram of Example 4 and Comparative Example 1.
[0188] Table 2 Electrochemical performance test results of solid electrolyte
[0189]
[0190] The charge and discharge performance test results in Table 2 show that the batteries assembled in the above embodiments all have a high discharge specific capacity. After 500 cycles, the capacity retention rate is still above 74%, and can reach up to 92.2%, such as Example 4, while the battery of the solid electrolyte in the comparative example shows extremely poor cycle stability. The capacity retention rate after 500 cycles is 65.2 for Comparative Example 1, and only 59.4% for Comparative Example 2. All the above results prove that the addition of MOF filler greatly improves the cycle performance of the battery. The tensile strength test results in Table 2 show that the polyurethane-based solid electrolyte membrane prepared in the embodiment has a tensile strength generally between 65-70MPa due to the hydrogen bond network and the strong MOF three-dimensional skeleton, such as 66.8MPa for Example 4, while the tensile strength of the comparative example is only between 50-55MPa, such as 54.1MPa for Comparative Example 1. The test results of the lithium ion migration number in Table 2 show that the test results of Examples 1 to 7 are significantly better than Comparative Examples 1 and 2.
[0191] Analysis shows that polyurethane is composed of soft segments and hard segments, in which the soft segment provides Li + The hard segments provide structural rigidity, e.g. Figure 1 and Figure 2 As shown; Figure 1 is a schematic diagram of the structure of polyurethane. Figure 2The figure is a schematic diagram of the synthesis of polyurethane. The soft segment molecular weights in Example 1 and Example 2 are different, and the result is that the solid electrolyte with a larger soft segment molecular weight has better ionic conductivity. For the polyurethane solid electrolyte with 10wt% plasticizer added, its overall ionic conductivity is higher than that of the polyurethane solid electrolyte with 5wt% plasticizer added. For Example 3 and Example 4, Example 4 added UiO-66-NH2, and the ionic conductivity (4.7*10 -4 S cm -1 ) and the lithium ion migration number (0.72) are higher than those in Example 3, which is attributed to the amino-modified UiO-66-NH2 particles and the UiO-66-NH2 three-dimensional skeleton, whose surface amino groups can form cross-linking sites with the polyurethane network, promote the dissociation of lithium salts and regulate the movement of anions, thereby improving the ionic conductivity and lithium ion migration number, and improving the charge and discharge stability, such as Figure 4 These hydrogen bond networks coupled with the strong MOF three-dimensional skeleton also provide the polyurethane-based composite solid electrolyte with ultra-high tensile strength and modulus, as shown in Figure 2. Figure 5 shown.
[0192] In summary, by comparing the above embodiments with the comparative examples, as shown in Table 2, it can be found that MOF particles and MOF three-dimensional skeletons have a significant effect on improving the ionic conductivity and lithium ion migration number of polyurethane-based solid electrolytes. The preparation method in this application significantly improves the electrochemical and mechanical properties of solid electrolytes.
[0193] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.
Claims
1. A polyurethane-based solid electrolyte, characterized in that: It includes a metal organic framework three-dimensional skeleton film and a composite polyurethane layer attached to the surface thereof; The metal organic framework three-dimensional skeleton film is a metal organic framework modified glass fiber cloth; The composite polyurethane layer comprises polyurethane and metal organic framework particles in situ embedded in a polymer network of the polyurethane; The repeating unit carbamate group in the polyurethane forms a hydrogen bond with the three-dimensional skeleton of the metal organic framework, synergistically improving the ion transport performance and mechanical properties.
2. The polyurethane-based solid electrolyte according to claim 1, characterized in that: The polyurethane is synthesized by reaction of isocyanate and diol; Preferably, the isocyanate is at least one of diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate, toluene diisocyanate and isophorone diisocyanate; Preferably, the diol is at least one of polytetrahydrofuran, polycarbonate diol, polypropylene glycol and polyethylene glycol; Preferably, the molecular weight of the diol is at least one of 800, 1000, 1200, 1500, 2000, 4000, 5000, 6000 and 8000.
3. The polyurethane-based solid electrolyte according to claim 1 or 2, characterized in that: The metal organic framework is at least one of MOF-5, MIL-53 (Al), HKUST-1, MIL-101, ZIF-1, ZIF-2, ZIF-3, ZIF-4, ZIF-5, ZIF-6, ZIF-7, ZIF-8, ZIF-9, ZIF-10, ZIF-22, ZIF-69, ZIF-90, NAFS-1, MIL-47, CAU-1, MIL-101 (Cr), CPO-27-Mg, CPO-27-Mn, CPO-27-Co, CPO-27-Ni, CPO-27-Zn, Mn (HCOO) 2, Co (HCOO) 2, Ni (HCOO) 2, MOF-74, zirconium-based MOF, and hafnium-based MOF; Preferably, the zirconium-based MOF is at least one of UiO-66(Zr), UiO-67(Zr), UiO-68(Zr), UiO-66-OH(Zr), UiO-67-OH(Zr), UiO-68-OH(Zr), UiO-66-NH2(Zr), UiO-67-NH2(Zr), UiO-68-NH2(Zr), UiO-66-4F(Zr), UiO-66-2F(Zr), UiO-66-CF3(Zr), UiO-66-SO3(Zr), UiO-67-SO3(Zr), and UiO-68-SO3(Zr); Preferably, the hafnium-based MOF is at least one of UiO-66(Hf), UiO-67(Hf), UiO-68(Hf), UiO-66-OH(Hf), UiO-67-OH(Hf), UiO-68-OH(Hf), UiO-66-NH2(Hf), UiO-67-NH2(Hf), UiO-68-NH2(Hf), UiO-66-4F(Hf), UiO-66-2F(Hf), UiO-66-CF3(Hf), UiO-66-SO3(Hf), UiO-67-SO3(Hf), and UiO-68-SO3(Hf).
4. The polyurethane-based solid electrolyte according to claim 1 or 2, characterized in that: The glass fiber cloth is at least one of glass fiber woven cloth, glass fiber non-woven cloth, and glass fiber filter membrane; Preferably, the unit weight of the glass fiber cloth is 10 to 200 g / m 2 , the thickness of glass fiber cloth is 10~100μm; Preferably, the metal organic framework three-dimensional skeleton film is a three-dimensional porous skeleton formed by in-situ growth of the metal organic framework on the glass fiber cloth; Preferably, the loading rate of the metal organic framework on the metal organic framework three-dimensional skeleton film is 5 to 30%; Preferably, the thickness of the polyurethane-based solid electrolyte is 30 to 250 μm.
5. The method for preparing the polyurethane-based solid electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are included: a) mixing diisocyanate, diol, lithium salt, organic solvent and catalyst under inert atmosphere, heating and stirring to obtain a prepolymer; b) adding a chain extender, a plasticizer and metal organic framework particles to the prepolymer, and continuing heating and stirring to obtain a polyurethane solution; c) coating the polyurethane solution on the metal organic framework three-dimensional skeleton film and drying it to obtain the polyurethane-based solid electrolyte.
6. The preparation method according to claim 5, characterized in that: In step a) and step b), the amount of isocyanate is 10 to 100 parts by weight, the amount of diol is 100 to 500 parts by weight, the amount of chain extender is 1 to 5 parts by weight, the amount of catalyst is 0.5 to 1 part by weight, the amount of lithium salt is 30 to 150 parts by weight, the amount of organic solvent is 500 to 1000 parts by weight, the amount of plasticizer is 5 to 50 parts by weight, and the amount of metal organic framework particles is 1 to 25 parts by weight; Preferably, the chain extender is at least one of 2,2-dihydroxymethylbutyric acid, bis(2-hydroxyethyl) disulfide, 1,4-butanediol, 2-hydroxyethyl acrylate, N-methyldiethanolamine, methylpropylene glycol, diethylene glycol and polycaprolactone triol; Preferably, the catalyst is dibutyltin dilaurate; Preferably, the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium trifluoromethanesulfonate; Preferably, the organic solvent is at least one of tetrahydrofuran, chloroform, N,N-dimethylformamide, butanone, dichloromethane and dimethyl sulfoxide; Preferably, the plasticizer is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, succinonitrile and 3-methyl-2-oxazolidinone.
7. The preparation method according to claim 5, characterized in that: In step a), the heating and stirring temperature is 50 to 80° C., the stirring speed is 600 to 1200 rpm, and the heating and stirring time is 8 to 15 hours; Preferably, in step a), the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; Preferably, in step b), the heating and stirring temperature is 50 to 80° C., the stirring speed is 600 to 1200 rpm, and the heating and stirring time is 2 to 5 hours; Preferably, in step c), the drying method is vacuum drying; Preferably, in step c), the vacuum drying is carried out at 60-100° C. for 12-24 hours.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method of the metal organic framework three-dimensional skeleton film comprises: immersing the surface treated glass fiber cloth in a metal organic framework precursor solution, heating, in-situ synthesizing the metal organic framework on the surface of the glass fiber cloth, and then washing and drying to obtain the metal organic framework three-dimensional skeleton film; Preferably, the surface treatment of the glass fiber cloth comprises soaking the glass fiber cloth in a solution of a surface treatment agent, and then taking it out and drying it, so as to obtain the surface-treated glass fiber cloth; Preferably, the surface treatment agent includes a silane coupling agent and / or dopamine; Preferably, the silane coupling agent is at least one of isobutyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, 3-aminopropyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy) silane and vinyl triethoxysilane; Preferably, the solution of the surface treatment agent is an aqueous solution of the surface treatment agent; Preferably, the solution of the surface treatment agent is obtained by dissolving the surface treatment agent in deionized water at a volume ratio or weight ratio of 1:200 to 1:5; Preferably, the glass fiber cloth is immersed in a solution of a surface treatment agent, specifically comprising: immersing the glass fiber cloth in the solution of the surface treatment agent for 0.01 to 24 hours; then, taking out the glass fiber cloth, rinsing it with deionized water and / or ethanol, and then drying it at 80 to 120° C.; Preferably, the method further comprises activating the prepared metal organic framework three-dimensional skeleton film in advance, and then coating the activated metal organic framework three-dimensional skeleton film with the urethane solution; Preferably, the activation treatment method is to heat the prepared metal organic framework three-dimensional skeleton film at 120 to 150° C. for 24 to 48 hours.
9. Use of the polyurethane-based solid electrolyte according to any one of claims 1 to 4 in lithium metal batteries or lithium ion batteries.
10. A lithium metal battery or a lithium ion battery, characterized in that: The polyurethane-based solid electrolyte according to any one of claims 1 to 4 is used.
Citation Information
Patent Citations
Solid electrolyte, and lithium metal anode and a preparation method thereof
CN112117488A
Polyurethane solid electrolyte as well as preparation method and application thereof
CN114195978A
Polyurethane-based solid electrolyte as well as preparation method and application thereof
CN114300740A
Glass fiber-based composite material and preparation method and application thereof
CN117691199A
Polyurethane based membranes and / or separators for electrochemical cells
CN103917569A
Cited By
Solid polymer electrolyte as well as preparation method and application thereof
CN118800955A
Preparation method of composite modified tertiary amine catalyst
CN122377546A
A method for preparing a composite modified tertiary amine catalyst
CN122377546B